Electrochemical corrosion of liquid phase sintered silicon carbide ceramics. Issue 3 (10th October 2011) - Sydow, U.; Sempf, K.; Herrmann, M.; Schneider, M.; Kleebe, H.‐J.; Michaelis, A.
Abstract Liquid‐phase sintered silicon carbide (LPS‐SiC) is silicon carbide ceramic which contains sintering additives forming a liquid phase during sintering. These additives segregate in the grain boundary phase during cooling. The usually used Al2O3 dissolves partially in the SiC‐grains and therefore changing the conductivity of the SiC (core rim structure). This study is focused on the electrochemical properties of LPS‐SiC with yttria and alumina as sintering additives. Electrochemical corrosion behaviour of LPS‐SiC has been determined by linear and cyclic voltammetry in acidic and alkaline solution. The effect of anodic oxidation on the material has been monitored by field emission scanning electron microscopy (FESEM) and energy dispersive X‐ray spectroscopy (EDX) as well as by atomic force microscopy (AFM). The core‐rim structure of the investigated materials plays a decisive role in the vulnerability towards corrosion. If oxidative attack was found to occur under anodic polarization, it happened preferentially in the rim region of the SiC‐grains, while the core of the SiC‐grains remained basically unaffected.